KESIAPAN GURU DALAM MENGADOPSI DAN MENGGUNAKAN ICT DALAM PEMBELAJARAN PAI: PROBLEM, DAMPAK DAN SOLUSINYA - Fadlin Fajri; Didi Maslan; Parentah Lubis; Trian Azhari Fadilah Sirait; Haidir (Universitas Yudharta Pasuruan, 2023)
In this article, we will analyze in depth the problems of teacher readiness in adopting and using ICT in PAI learning and the impacts that arise. In addition, several solutions and strategies that can be implemented to increase teacher readiness in integrating technology effectively in PAI learning will also be explained. The methodology used in this study is a qualitative method with the aim of exploring the problems of teacher readiness in ICT-based Islamic Religious Education learning, the impacts that arise, and solutions in adopting and using ICT in Islamic Islamic Education learning. The results of the research conducted show that teacher problems in implementing ICT-based PAI learning include unsupportive curricula, lack of ICT resources, lack of principal support, limited ICT knowledge and skills, concerns about technological complexity, and resistance to changes from traditional learning methods. . While the impacts that arise from these problems include a decrease in the quality of learning and inequality of understanding, and low professional development. Meanwhile, solutions and strategies that can be implemented to address these issues include training and professional development tailored to the needs of teachers, provision of adequate resources and technical support, as well as collaboration and sharing of knowledge between teachers. Keywoards : Teacher Readiness, PAI Learning, ICT